2017
DOI: 10.1093/ndt/gfx053
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkalaemia prevalence, recurrence and management in chronic haemodialysis: a prospective multicentre French regional registry 2-year survey

Abstract: HK was found to be highly prevalent and recurrent in this regional registry despite the widespread and dynamic prescription of low-K dialysis baths and K binders. More effective potassium mitigating strategies are eagerly warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 14 publications
1
40
1
Order By: Relevance
“…The prevalence of HK, when defined as sK > 6 mmol/L, in HD ranges between 10 and 20% in the DOPPS (The Dialysis Outcomes and Practice Patterns Study) survey and DaVita data [ 28 , 29 ], while in PD it is about 7%, when defined as sK > 5.5 mmol/L [ 29 ]. However, a recent study has shown that the overall percentage of HD patients experiencing HK anytime over a 2-year follow-up period can be as high as 74% for sK > 5.1 mmol/L, 58% for sK > 5.5 mmol/L and 35% for sK > 6 mmol/L [ 9 ]. On the other hand, more than 25% PD patients have time-averaged sK < 4.0 mEq/L, a level that is associated with a significant increase in mortality risk in this population.…”
Section: Hyperkalemia In Dialysis Patientsmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence of HK, when defined as sK > 6 mmol/L, in HD ranges between 10 and 20% in the DOPPS (The Dialysis Outcomes and Practice Patterns Study) survey and DaVita data [ 28 , 29 ], while in PD it is about 7%, when defined as sK > 5.5 mmol/L [ 29 ]. However, a recent study has shown that the overall percentage of HD patients experiencing HK anytime over a 2-year follow-up period can be as high as 74% for sK > 5.1 mmol/L, 58% for sK > 5.5 mmol/L and 35% for sK > 6 mmol/L [ 9 ]. On the other hand, more than 25% PD patients have time-averaged sK < 4.0 mEq/L, a level that is associated with a significant increase in mortality risk in this population.…”
Section: Hyperkalemia In Dialysis Patientsmentioning
confidence: 99%
“…HD patients should restrict their daily dietary K to 2–3 g [ 36 ]. Because HK is currently and frequently recognized in the dialysis setting, it is quite clear that current strategies do not allow the full control of HK [ 9 ].…”
Section: Hyperkalemia In Dialysis Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this K þ -binding agent has been associated with gastrointestinal intolerance and serious gastrointestinal complications. [71][72][73] The US Food and Drug Administration warns against using SPS with sorbitol because of cases of intestinal necrosis and other serious gastrointestinal events (e.g., bleeding, ischemic colitis, and perforation). 74 They also recommend separating the administration of SPS from other oral medicines by $3 hours because of the nonspecific binding properties of SPS.…”
Section: Nondialysis Options For Managing Hyperkalemiamentioning
confidence: 99%